The Effect of P-Cymene on Glucose, Insulin, Antioxidant Power, and the Level of AKT Gene mRNA in Streptozotocin-Induced Diabetes Model in Male Wistar Rats - Maryam Arabloei Sani; Zahra Hajebrahimi; Parichehreh Yaghmaei; Nasim Hayati Roodbari (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: Diabetes is a main metabolic disorder in middle-aged and older people. Oxidative stress can interfere with insulin signaling and are directly relevant to the incidence of diabetes. The AKT signaling pathways plays a critical role in regulating glucose homeostasis and proliferation of β cells. P-cymene is an aromatic monotropene with antioxidant and anti-inflammatory properties. In the present study, the therapeutic effects of p-cymene on blood glucose and insulin levels, the antioxidant power of serum (FRAP assay) and the expression of AKT mRNAs in streptozotocin-induced diabetic rats were investigated. Materials and Methods: Diabetes was induced using the injection of 55 mg/kg streptozotocin in male Wistar rats. Histological, biochemical, and real-time PCR analyses were done to study the effects of metformin (55 mg/kg) and p-cymene (25, 50, and 100 mg/kg) on levels of glucose, insulin, oxidative stress status, and the expression of AKT mRNA. Results: Streptozotocin increased serum levels of glucose and decreased serum levels of insulin, the antioxidant power of serum, pancreas levels of AKT mRNA, and β island size. Administration of metformin or p-cymene improved the levels of glucose, insulin, AKT mRNA, β island size, and antioxidant power in an independent manner of dose. Conclusion: These results suggest that p-cymene has hypoglycemic, hyperinsulinemia, and antioxidant properties. It can regulate Akt signaling pathway. Therefore, it may be suggested for the diabetes therapy alone or in combination with metformin.